Pengetahuan Remaja Putri terhadap Pemeriksaan Payudara Sendiri (SADARI) - Junay Darmawati; Lidya Fransisca; Adriani Adriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between knowledge and young women's attitudes toward breast self-examination at the Midwifery Academy of Al-Su'aibah Palembang. This research method uses an analytical survey method. The results of the univariate analysis study were obtained from the fact that out of 55 respondents, 19 respondents (34.5%) performed breast self-examination, and 36 respondents (65.5%) did not. 23 respondents (41.8) had good knowledge of young women, and 32 respondents (58.2) had poor knowledge. Bivariate analysis using the chi-square statistical test showed a significant relationship between knowledge of breast self-examination and ρ value = 0.01 ≤ ɑ (0.05). In conclusion, there is an important relationship between knowledge of breast self-examination at the Al-Su'aibah Midwifery Academy Palembang. Keywords: Breast Self Examination, Knowledge, Young Women